Identification of Enteric Bacterial Pathogens in Beverages Sold By Hawkers around Jatinangor, Bandung - Teow Sheng Hao; Yanti Mulyana; Bachti Alisjahbana (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Water is essential for life and is considered as a medium for the propagation and dissemination of bacteria. Water-borne disease is one of the problems in Indonesia, therefore, this study was conducted to explore the presence of enteric bacterial pathogens in the beverages sold by hawkers.Methods: A descriptive laboratory method was conducted in September 2015 Beverages were collected from hawkers that were randomly chosen around Jatinangor using sterile containers, and brought to the laboratory within 1 hour. The beverages were incubated on Mueller Hinton Broth, followed by culturing on MacConkey Agar. The organisms were identified using Gram Staining, Kliger Test, Motility-Indole-Urease test and Citrate test.Results: Out of 30 samples collected, 2 of the samples were tested positive for enteric bacterial pathogen Salmonella paratyphi. Furthermore, Klebsiella pneumoniae (n=12), Enterobacterspp (n=10) Alcaligenes faecalis (n=3) and Pseudomonas spp. (n=3) were detected in the samples.Conclusions: The Salmonella paratyphi as enteric bacterial pathogen found in the beverages sold by hawkers has potential to cause water-borne disease. Education to hawkers need to be enhanced.